Pulmonary vein isolation for atrial fibrillation patients with reduced left ventricular ejection fraction. (25th November 2020) - Ikenouchi, T; Inaba, O; Kono, T; Murata, K; Takamiya, T; Inamura, Y; Sato, A; Nitta, J; Takahashi, Y; Goya, M; Sasano, T
Abstract:  : Background/Introduction Pulmonary vein isolation (PVI) is a cornerstone of curable treatment for atrial fibrillation (AF). Left ventricular (LV) ejection fraction (EF) occasionally improves after PVI in AF patients with reduced LVEF (rEF), the mechanism of which is not fully understood. CASTLE-AF trial have demonstrated that PVI with radiofrequency (RF) catheter for AF patients with rEF can reduce their mortality and heart failure. Nevertheless there are limited data about the clinical outcome of the PVI for patients with impaired LV function. Purpose: This study was to evaluate the efficacy of PVI and improvement of LVEF after the procedure in AF patients with rEF. Methods: A total of 2709 consecutive AF patients (age 65±39 y/o, male 67%) underwent their first PVI with cryoballoon or RF catheter in our facility from April 2014 to March 2019, and retrospectively analyzed. All the patients underwent echocardiogram before and half to one year after the procedure. Patients with LVEF under 40% before the PVI were selected (n=111) and divided into two groups based on whether there were specific etiologies of LV function impairment (group A) or not (group B). Results: There were no significant difference in mean LVEF between group A (n=40) and group B (n=71) (32±6% vs 33±6%, p=0.12). The major etiology of rEF in group A were old myocardial infarction (n=20, 18%), hypertensive heart disease (n=6, 5.4%), and dilated cardiomyopathy (n=5, 4.5%). After mean follow-up of 2.7 years, there were no significant difference in clinical outcome after the procedure between two groups (1-year Kaplan–Meier event rate estimates; 72.2% vs 72.9%; p=0.85). The change amounts of LVEF after the PVI were significantly higher in group B (20±14%) compared to group A (2±10%) (p<0.001). Multivariable Cox regression analysis revealed that age was the independent significant predictors of EF improvement over 10% in group B (p=0.048). Conclusions: In AF patients with reduced LVEF, there were no significant difference in efficacy of PVI between those who have specific etiologies of LV function impairment other than AF and who have not. The improvement of LVEF after PVI was significantly larger in patients without specific etiologies compared to those with. Funding Acknowledgement: Type of funding source: None